Pemikiran Pendidikan Islam - Wulandari, Ayu; Sri Jumini (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
Education has  such  an  importantrole  in  human  life,  because  the  essence  of education itself is to humanize and mature humans, so that they become fully human. Education  is  a  process  of  guiding  humans  to  become  fully  human  and  naturally  as human beings who are the creation of Allah SWT. In education, the main thing that must be prepared is to formulate goals. With this aim, the educational process will be directed  and  carried  out  in  a  systematic  and  organized  manner so as to produce education that meets expectations and does not deviate from the norms of life in society. The purpose of Islamic education cannot be separated from the purpose of human life as a servant of Allah, forming a Muslim person who truly believes in Allah and whose whole life is oriented to Allah alone. The aim of Islamic education in essence is to make humans  as  servants  who  truly  believe  and  fear  Allah  which  is  reflected  in  their personality  who has noble  character,  both  in  living  in  society  and  towards  the environment or the universe. Thus, the purpose of Islamic education is based on the purpose of human life in this world as a Muslim. In the Koran, humans have at least three goals in life, namely to worship, to become caliphs and to know each other, in the sense of achieving a harmonious life in society. In the context of his relationship with  his  Lord,  humans  are  servants  of  Allah  who  have  the  obligation to  fulfill  His servitude and devotion. Whereas in the context of relations with the universe he is the caliph,  as  the  regulator  and  guardian  of  the  universe. And to create a peaceful  and prosperous universe, it is necessary to have shared responsibility in creating a peaceful world order. To make humans as pious servants, it needs a process through education. Thus,  Islamic  education is a tool to  realize  the purpose of  human  life  in  this  world. Because without education, humans will not be able to become educated human beings so as to achieve the degree of pious